1992
DOI: 10.1007/bf01888544
|View full text |Cite
|
Sign up to set email alerts
|

Management of diffuse esophageal spasm with balloon dilatation

Abstract: Of 1200 patients referred to the esophageal laboratory at Guy's Hospital for investigation of suspected esophageal motility disorders, 61 (5.1%) were diagnosed as diffuse esophageal spasm. Twenty of these patients whose symptoms were severe did not respond to conservative treatment and were treated by balloon dilatation. Results were good in 14 and poor in six patients, which included one esophageal perforation. Diffuse esophageal spasm was diagnosed where more than 30% nonperistaltic activity was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 8 publications
1
18
0
1
Order By: Relevance
“…Using the criterion of 30% nonperistaltic contractions to diagnose esophageal spasm, the authors identified and included 20 patients with esophageal spasm in a study to evaluate the effects of conventional (< 20 mm) balloon dilatation. Fourteen patients (70%) reported good clinical improvement, whereas the other six patients did not, including one esophageal perforation after balloon distention [44]. Three of the nonresponders underwent full-length myotomy, with relief of symptoms being reported in two patients.…”
Section: Dilatations (Rigid Dilators or Small-diameter Balloons)mentioning
confidence: 90%
See 1 more Smart Citation
“…Using the criterion of 30% nonperistaltic contractions to diagnose esophageal spasm, the authors identified and included 20 patients with esophageal spasm in a study to evaluate the effects of conventional (< 20 mm) balloon dilatation. Fourteen patients (70%) reported good clinical improvement, whereas the other six patients did not, including one esophageal perforation after balloon distention [44]. Three of the nonresponders underwent full-length myotomy, with relief of symptoms being reported in two patients.…”
Section: Dilatations (Rigid Dilators or Small-diameter Balloons)mentioning
confidence: 90%
“…• Irving et al [44] reported on the effects of balloon dilatation in a group of 20 patients from Guy's Hospital in London with severe symptoms that did not respond to conservative treatment. Using the criterion of 30% nonperistaltic contractions to diagnose esophageal spasm, the authors identified and included 20 patients with esophageal spasm in a study to evaluate the effects of conventional (< 20 mm) balloon dilatation.…”
Section: Dilatations (Rigid Dilators or Small-diameter Balloons)mentioning
confidence: 97%
“…Pneumatic dilation has been employed in the treatment of spastic disorders of the esophagus with some reports showing favorable results [62], but it is not known if the reported improvement was due to the inclusion of patients with achalasia.…”
Section: Endoscopic Treatmentmentioning
confidence: 99%
“…Although the rationale is unclear, some success has been reported in treating spastic disorders with dilation [35]. However, an important caveat to this is that it is completely uncertain as to whether patients who benefitted by pneumatic dilation would not be more properly categorized as having spastic achalasia or achalasia with esophageal compression, emphasizing the need for accurate manometric classification.…”
Section: Endoscopic Treatmentmentioning
confidence: 99%